Leadership – not followership – determines performance in ant teams - Thomas O. Richardson (Nature Portfolio, 2021)
Richardson et al. investigate the relationship between task performance and teamwork in ant colonies. Targeted removals of prominent leaders and followers during ‘tandem running’ - a cooperative team task in which one ant physically leads another to a resource - reveal that leadership, and specifically the consistency of leaders, influences tandem performance but ‘followership’ does not.